ANALISIS INTERNAL DAN EKSTERNAL KESIAPAN RSUD H. ABDUL AZIZ MARABAHAN UNTUK PENERAPAN BADAN LAYANAN UMUM DAERAH - , Candra Wijaya, S.Si,Apt; , Prof. Dr. Basu Swastha Dharmmesta, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Base on the Minister of Domestic Affairâs Rules No. 61, 2007, it gives an opportunity to RSUD H. Abdul Aziz Marabahan (RSUD HAAM) to be Regional Public Service Institution (Badan Layanan Umum Daerah/BLUD in Bahasa) which has greater authonomy on financial management to cope the current problems and increase their work performance. In the process of converting the status, some analysis concerning internal and external condition were done to know the strategic factors in customizing alternative strategies implementation of BLUD. Purpose: a. To analyse internal and external condition of RSUD HAAM in customizing alternative strategic implementation of BLUD